Implementación de un sistema de costos por procesos de los derivados de la leche y su incidencia en la rentabilidad de la asociación de agricultores agropecuarios de “Pucayacu”, cantón la maná periodo junio-diciembre 2013 - Pazquel Barroso, Yessenia Pamela (2015)
This research was developed in the Association of agricultural farmers "Pucayacu" located in the rural parish of the same name in Canton La Maná dedicated to the production of milk derivatives, the main objective of the research is the application of cost accounting for production processes in the second half of 2013 which will improve the Administrative and Financial Management in the Company, with the purpose of determining the object of study was developed market analysis, the main categories were identified, was also applied an exploratory research that allowed to know the problem to develop it was used a descriptive method considering that characterized the industry of study with beneficiaries, processes, techniques and evaluation of variables. It was necessary to know the production process of dairy products to certify the quality with which the work is done.